Cross-Contamination and Biofilm Formation by Salmonella enterica Serovar Enteritidis on Various Cutting Boards - Dantas, Stefani T. A. [UNESP]; Rossi, Bruna F. [UNESP]; Bonsaglia, Erika C. R. [UNESP]; Castilho, Ivana G. [UNESP]; Hernandes, Rodrigo T. [UNESP]; Fernandes, Ary [UNESP]; Rall, Vera L. M. [UNESP] (Mary Ann Liebert, Inc, 2018)
Cross-contamination is one of the main factors related to foodborne outbreaks. This study aimed to analyze the cross-contamination process of Salmonella enterica serovar Enteritidis from poultry to cucumbers, on various cutting board surfaces (plastic, wood, and glass) before and after washing and in the presence and absence of biofilm. Thus, 10 strains of Salmonella Enteritidis were used to test cross-contamination from poultry to the cutting boards and from thereon to cucumbers. Moreover, these strains were evaluated as to their capacity to form biofilm on hydrophobic (wood and plastic) and hydrophilic materials (glass). We recovered the 10 isolates from all unwashed boards and from all cucumbers that had contacted them. After washing, the recovery ranged from 10% to 100%, depending on the board material. In the presence of biofilm, the recovery of salmonellae was 100%, even after washing. Biofilm formation occurred more on wood (60%) and plastic (40%) than glass (10%) boards, demonstrating that bacteria adhered more to a hydrophobic material. It was concluded that the cutting boards represent a critical point in cross-contamination, particularly in the presence of biofilm. Salmonella Enteritidis was able to form a biofilm on these three types of cutting boards but glass showed the least formation.
Keywords: biofilm; cross-contamination; csgD and adrA genes; cutting boards; Salmonella Enteritidis